Evaluating the Opinions of the Supreme Court and the Council of State on “Informed Consent (Assent)” in Compensation Cases Filed with Medical Malpractice Claim - Vural, Talip; Erbaş, Melike (The Bulletin of Legal Medicine, 2024)
Objective: In our study; we aimed to contribute to the literature by raising the awareness of our physicians on the importance and necessity of the informed consent form by evaluating the reversing decisions of the high courts. Methods: The decisions made by the relevant departments of the Council of State and the Supreme Court of Appeals between 2013 and 2022 regarding the cases of pecuniary and non-pecuniary damages brought against malpractice claims were examined. 102 decisions were impaired due to the absence or lack of an informed consent form included in our study. Results: A total of 72.5% of all the lawsuits filed in the civil and criminal jurisdictions together with administrative jurisdictions originate from the surgical branches, 100% of the symptoms occurring after the medical procedures were defined as complications, 20.6% of the cases were not prepared with an informed consent form, 24.5% were incompletely drawn up, 3.9% were filed by the relatives of the patients. It was determined that the decisions given by the first instance courts were overturned by the high courts due to incomplete examination, without investigating the informed consent form in 51% of the cases. Conclusion: Even if the deficits that occur after the medical intervention are accepted as complications, decisions are made against the physicians and hospital administrations by the high courts as a result of the fact that the informed consent forms are not prepared, are incompletely prepared, and signed by the relatives of the patients.